Levels of Soluble NKG2D Ligands and Cancer History in Patients Starting Hemodialysis - Nagai, Kei; Tawara, Takashi; Usui, Joichi; Ebihara, Itaru; Ishizu, Takashi; Kobayashi, Masaki; Maeda, Yoshitaka; Kobayashi, Hiroaki; Yamagata, Kunihiro (Frontiers in Nephrology, 2022)
Background: Immune dysfunction in hemodialysis patients is partially due to NK cell impairment. Ligands for NK activating receptors such as NKG2D expressed on cancer cells are involved in NK cell dysfunction and can lead to cancer development. Methods: A cohort with 370 patients who started hemodialysis (HD) was investigated. Serum levels of soluble NKG2D ligands were measured. Cancer history was defined as any cancer diagnosis at induction and hospitalization and death due to cancer during 2-year follow-up. Results: Sixty-two patients with and 308 patients without a cancer history showed mostly comparable biochemical parameters and uremic status at HD induction. Soluble MICB, ULBP-1, and ULBP-2 were detected in sera from most patients starting HD rather than MICA, the most representative NKG2D ligand. Measured NKG2D ligands, except for ULBP-1, were strongly correlated with each other. Correlations between NKG2D ligands and renal function were significant but modest in patients starting HD. Cancer history did not have any impact on levels of soluble NKG2D ligands. Discussion: Even though this investigation lacked a control cohort and serial measurement of parameters, expression patterns of NKG2D ligands were comprehensively described, and the significance of cancer in patients starting HD was elucidated for the first time. Elevated levels of soluble NKG2D ligands occurred potentially due to complex mechanisms of oxidative stress, with insufficient metabolism and excretion in a uremic milieu, but they might mask the significance of elevations in serum levels of soluble NKG2DLs in patients with a cancer history.